(untitled) (Spagna contemporanea. Rivista semestrale di storia, cultura, istituzioni, 1998)
Introducción al 98 The 1898 war began in Cuba and in the Philippine Islands, two colonies that declared for independence against the State, but not against Spanish civilisation. The imperialistic Yankee intervention provoked the Desastre, and after that a widespread pessimism, quite evident within the Regeneracionistas and the ’98 Generation. This was the name given to a group of writers who created a new language, and passed with that from social protest to aesthetics. Notwithstanding all its contradictions, the group remained loyal to the people during his most tremendous hour.